The Rhetoric of Travel and Exploration : a New “Nature” and the Other in Early to mid- Eighteenth-Century English Travel Collections - Matthew Binney (Revue LISA)
The aim of this paper is to examine the shifting spirit and rhetoric of English travel collections between the end of the 16th century and the early 18th century. Whereas writers like Hakluyt, the Churchills or Harris tended to enfold peoples and nations within the determinate telos of Christendom, Campell’s, Green’s and Button’s travel collections are characterized by a new discourse which draws upon the work of Hobbes, Locke and Spinoza. In the new framework, trade and commerce take precedence over Christianity. Reason and experience indicate that a spirit of commerce, rather than religion, provides the connection between the countries and nations of the world.